Management of the Process of Reception, Storage and Delivery of Fuels at the Slaughtering Commercialization Company - Sánchez Suárez, Yasniel (2025)
Delays in the unloading and receiving of fuels due to low logistical capacity and infrastructure create bottlenecks and affect the distribution of crude oil. The objective of the research is to analyze the fuel reception, storage, and delivery process in a Cuban fuel distribution company. The methodology is descriptive and quantitative, with a systematic approach to assess the potential impacts of solutions on stakeholders, based on a bibliographic study, as well as an analysis using the General Problem-Solving Method. As a result of the investigation, non-compliance with the temperature parameters required by customers was detected, since the pipes lack the necessary coating to maintain temperature. Based on the deficiencies identified in the process, a set of actions is proposed, focusing on the replacement, repair, and installation of equipment, as well as ensuring the logistical supply of spare parts.